Aromatic Thiolate-Protected Series of Gold Nanomolecules and a Contrary Structural Trend in Size Evolution - Sakthivel, Naga Arjun; Dass, Amala (Accounts of chemical research, 2018)
Conspectus Thiolate-protected gold nanoparticles (AuNPs) are a special class of nanomaterials that form atomically precise NPs with distinct numbers of Au atoms (n) and thiolate (−SR, R = hydrocarbon tail) ligands (m) with molecular formula [Au n (SR) m ]. These are generally termed Au nanomolecules (AuNMs), nanoclusters, and nanocrystals. AuNMs offer atomic precision in size, which is desired to underpin the rules governing the nanoscale regime and factors affecting the unique properties conferred by quantum confinement. Research since the 1990s has established the molecular nature of these compounds and investigated their unique size-dependent optical and electrochemical properties. Pioneering work in X-ray crystallography of Au102(SC6H4COOH)44 and Au25(SC2H4Ph)18 – revolutionized the field by providing significant insight into the structural assembly of AuNMs and surface protection modes. Recent discoveries involving bulky and rigid ligands to favor crystal growth as a solution to the nanostructure problem have led to crystal structure determinations of several AuNMs (n = 18 to 279). However, there are several open questions, such as the following: How does the structure evolve with size? Does the atomic structure determine the properties? What determines the atomic structure? What factors govern the stability: geometry or electronic properties or ligands? Where does the molecule-to-metal transition occur? Answering these questions requires the elucidation of governing rules in the nanoscale regime. In this Account, we discuss patterns and trends observed in structures, growth, and surface protection modes of 4-tert-butylbenzenethiolate (TBBT)-protected AuNMs and others to answer some of the important open questions. The TBBT series of AuNMs comprises Au28(SR)20, Au36(SR)24, Au44(SR)28, Au52(SR)32, Au92(SR)44, Au133(SR)52, and Au279(SR)84, where Au28 to Au133 are molecule-like with discrete electronic structures and Au279 exhibits metal-like properties with a surface plasmon resonance (SPR) at 510 nm. The TBBT series of AuNMs have dihedral symmetry, except for Au133(SR)52, which has no symmetry. We synthesize the scaling law and the rules of surface assembly, one-, two-, and three-dimensional growth patterns, the structural evolution trend, and an overarching trend for diverse types of thiolate-protected AuNMs. This Account sheds light on a new perspective in structural evolution for the TBBT series based on observations, namely, face-centered cubic (FCC) to decahedral to icosahedral to FCC, which contrasts with the contemporary understanding of the structural evolution of naked metal clusters (NMCs) from icosahedral to decahedral to FCC. We also hope that this Account will be of pedagogical value and spur further experimental and computational studies on this wide range of structures to delineate the underlying stability factors in the magic series.